CONGENITAL ANOMALIES: PREVALENCE OF CONGENITAL ABNORMALITIES IN 2ND TRIMESTER OF PREGNANCY IN MADINA TEACHING HOSPITAL, FAISALABAD ON GRAY SCALE ULTRASOUND - Nayab Alia; Irshad Ahmed (Journal of University Medical & Dental College)
ABSTRACT Objectives: To evaluate the antenatal prevalence of major congenital anomalies and malformation patterns in our hospital population Study Design: Cross-sectional observational. Settings: Radiology Department of Madina Teaching Hospital Faisalabad. Duration: 12 months from January 2009, to December 2009 Sample size: 2890. Material and Methods: The patients, who under went regular obstetrics ultrasound from, were recruited. Data of Antenatal ultrasounds was statistically analyzed on structured data collection form to determine the prevalence of congenital anomaly in 2nd trimester. Results: We diagnosed 86 cases of fetal anomalies. The antenatal prevalence of congenital anomalies was 29.75 per 1000 and 2.97%. The mean maternal age and mean gestational age at diagnosis was 26.5 years and 24 weeks respectively. Out of the total (N=86), 15.6% occurred in women above the age of 35 years. Central nervous system and Musculo-skeloton were commonly diagnosed, fallowed genitourinary, renal and miscellaneous (hydrops fetalis, pleural effusion) etc. However, facial and heart defects rarely found or more commonly missed. Conclusion: The prevalence of major congenital anomalies in our population appears to be similar to international figures AS 2.97%. The study showed the preponderance of neural tube defects. In contrast about a quarter of musculo-skeleton and genitourinary, however no facial defects and cardiac defect were detected because of high patient turn out, have no 3D/4D and Doppler ultrasound. Based on these findings we recommend that the obstetricians should advised, regular ultrasound at least at 18-23 weeks by consultant radiologist at low risk patients.